PENETAPAN HARGA JUAL SEBAGAI STRATEGI PEMASARAN PRODUK BUNGA KAWAT BULU PADA UMKM MOYGIFT - Alisa Sandrina Ramadhani; Liza Nora (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
This study aims to evaluate the selling price determination of pipe cleaner flower products at MoyGift MSME as part of its marketing strategy and business sustainability efforts. The study employed a qualitative approach using an evaluation research design. Primary data were collected through observation, documentation, and interviews with the business owner and production personnel. The findings indicate that production management encompasses production planning, production control, process improvement, and quality management. However, the determination of selling prices is still conducted in a relatively simple manner and does not fully incorporate all production cost components. Based on the simulation of cost of goods manufactured, the production cost was calculated at IDR 10,590 per unit. With a selling price of IDR 15,000 per unit, the business earns a profit of IDR 4,410, representing a profit margin of approximately 29%. The study recommends adopting a more comprehensive costing approach to ensure more accurate pricing decisions and enhance business competitiveness.Keywords: Selling Price, Cost of Goods Manufactured, Marketing Strategy, Production Management, MSMEs.